The Role of Housewives in Supporting Children's Education in Environment II Ara Tunggal District, Selesai District, Langkat Regency - Dea Puspita Sari; Juliani; Dio Septiawan; Fiqi Fahlevi (Yayasan Zia Salsabila, 2025)
The aim of this research is to explore and describe in depth the role of housewives in supporting their children’s education within this community, including the forms of support they provide, the obstacles they face, and the strategies they employ to overcome those challenges. This study uses a qualitative approach with a descriptive method. Data were collected through observation, in-depth interviews, and documentation. Informants were selected purposively, specifically housewives who are actively involved in their children’s education, both at home and in the surrounding environment. Data analysis techniques include data reduction, data presentation, and conclusion drawing. The findings reveal that housewives make significant contributions to their children’s education, both academically such as assisting with studying, helping with school assignments, and maintaining communication with teachers and non-academically, such as providing emotional support and shaping moral character. Values such as honesty, responsibility, and discipline are instilled through role modeling and intensive communication. Despite facing challenges such as limited time, knowledge, and learning facilities, these mothers actively seek solutions through discussions with teachers, parenting workshops, and peer support groups. In conclusion, housewives play a strategic role in holistically supporting their children’s education. Therefore, it is essential to enhance their capacity and awareness in fulfilling this role to foster a synergistic educational environment between home and school.